2020
DOI: 10.3389/fmicb.2019.02835
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Bacterial Wilt Disease Through Complex Interaction Between Tomato Plant, Antagonists, the Indigenous Rhizosphere Microbiota, and Ralstonia solanacearum

Abstract: Ralstonia solanacearum (biovar2, race3) is the causal agent of bacterial wilt and this quarantine phytopathogen is responsible for massive losses in several commercially important crops. Biological control of this pathogen might become a suitable plant protection measure in areas where R. solanacearum is endemic. Two bacterial strains, Bacillus velezensis (B63) and Pseudomonas fluorescens (P142) with in vitro antagonistic activity toward R. solanacearum (B3B) were tested for rhizosphere competence, efficient b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 65 publications
8
38
0
1
Order By: Relevance
“…For example, Arabidopsis roots in response to a leaf pathogen infection attract Bacillus subtilis into the rhizosphere 49 . In the current study, the most enrichment in IT20 samples was recorded for the genus Devosia affiliated to Gammaproteobacteria, it was previously described that this genus is increased in response to B. velezensis and P. fluorescens , involved in biocontrol activity against R. solanacearum on tomato 50 . Another increase in relative abundance was recorded for the genus Gallionella that was previously described as a member of the core microbiome of the wheat healthy plant 23 .…”
Section: Discussionsupporting
confidence: 56%
“…For example, Arabidopsis roots in response to a leaf pathogen infection attract Bacillus subtilis into the rhizosphere 49 . In the current study, the most enrichment in IT20 samples was recorded for the genus Devosia affiliated to Gammaproteobacteria, it was previously described that this genus is increased in response to B. velezensis and P. fluorescens , involved in biocontrol activity against R. solanacearum on tomato 50 . Another increase in relative abundance was recorded for the genus Gallionella that was previously described as a member of the core microbiome of the wheat healthy plant 23 .…”
Section: Discussionsupporting
confidence: 56%
“…The treatments of P. fluorescens Pf3 + T. longibrachiatum UNS11 were recorded highest wilt protection of 62% as compared to control treatment (97%). Our research outcomes authenticate earlier reports that in the control of bacterial wilt, the use of beneficial microbes in combination treatments was more effective than individual agents (Thilagavathi et al 2007 andElsayed et al 2020). The present results agreed with the R. solanacearum wilt disease reduction in tomato plants by treatment with Bacillus sp.…”
Section: Effect Of Seed Treatment Combination With Pgpr and Trichodersupporting
confidence: 89%
“…However, the majority of studies revealed only transient establishment or low abundance of the microbial inoculants during plant growth ( Scherwinski et al, 2008 ; Schreiter et al, 2014b ; Eltlbany et al, 2019 ). In order to understand establishment efficiency, it is important to consider rhizosphere and rhizoplane colonization patterns of the inoculant ( Götz et al, 2006 ; Elsayed et al, 2020 ). A successful establishment depends on strain traits ( Adesina et al, 2009 ), application mode ( Götz et al, 2006 ; Schmidt et al, 2012 ), and on the structure of the target microbiome ( van Elsas et al, 2012 ).…”
Section: Interactions Of Microbial Inoculants With the Plant And Its Microbiomementioning
confidence: 99%
“…Similar effects were observed in tomato plants infected with Ralstonia solanacearum B3B through the inoculation of Bacillus velezensis B63 or Pseudomonas fluorescens P142. Here, a microbiome shift toward genera that comprise multiple strains with plant growth promoting activity such as Arthrobacter and Gaiella (Actinobacteria ) or Ochrobactrum ( Alphaproteobacteria ) was observed ( Elsayed et al, 2020 ). Fusarium stalk rot in maize caused by Fusarium graminearum can be controlled via application of Trichoderma harzianum CCTCC-RW0024, which resulted in an increase of plant growth promoting Acidobacteria ( Saravanakumar et al, 2017 ).…”
Section: Interactions Of Microbial Inoculants With the Plant And Its Microbiomementioning
confidence: 99%
See 1 more Smart Citation